Advances in Pancreatic Biomarker Measures: A Novel Approach to An Obscure Organ. Issue 10 (October 2016) - Conwell, Darwin L; Whitcomb, David C
Abstract : N/A: The pancreas remains a challenging organ to assess because of its retroperitoneal locations and cost of accessing the pancreatic duct for collection of biological samples. A novel and potentially useful approach to analysis of pancreatic juice proteins has been developed by Rocker et al. ( Clin Transl Gastroenterol 7: e174; doi:10.1038/ctg.2016.27) using whole‐gut lavage fluid from a colonoscopy prep. The widespread use of colonoscopy for colon cancer screening provides the opportunity to also screen the patient for benign and malignant pancreatic diseases using the fluid waste. New approaches are needed to assessing the pancreas, and wastes should not be wasted.